PSIKOLOGI TOKOH DALAM NOVEL SERANGKAI KARYA VALERIE PATKAR: PSIKOANALISIS SIGMUND FREUD - Sundari Ayu Wandira Indah Surya; Irianto Ibrahim; sulfiah (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to describe the psychological aspects of the characters in the novel Serangkai by Valerie Patkar through the lens of Sigmund Freud’s psychoanalytic theory. The analysis focuses on the three components of personality structure: the id, ego, and superego. This is a qualitative descriptive study using a library research design. The primary data source is the novel Serangkai, published by Bhuana Ilmu Populer in 2021, consisting of 400 pages. The study adopts a literary psychology approach, emphasizing the internal psychological conditions of the characters as reflected in the narrative, without involving the author's background or readers’ responses. Data were collected through content analysis by identifying and interpreting textual evidence that reflects the dynamics of the id, ego, and superego based on Freud’s theory. The findings reveal that the characters in Serangkai undergo complex internal conflicts resulting from the interaction among their instinctual drives (id), rational thinking (ego), and moral conscience (superego). These psychological dynamics significantly influence their behaviors and decisions throughout the story.